'Do we need doulas...?' - Perspectives of maternity care managers on the role of doulas in Poland - Katarzyna Wójcik‐Brylska; Paulina Pawlicka; Urszula Tataj‐Puzyna; Beata Szlendak; Barbara Baranowska (Wiley, 2023)
Abstract Aim The purpose of this study was to analyse perinatal care managers' perspectives on the role of doulas in Poland and to consider how managers' perspectives might affect the opportunities for doulas to practice in individual hospitals. Design This is a qualitative descriptive study. Method The total of 17 hospitals was selected for the study. Semi‐structured interviews were conducted with 11 manager staff members. Results Three groups of facilities were identified: '0' (n = 6) - refused to give interviews, 'A' (n = 8) - marginal experience in working with doulas, and 'B' (n = 3) - regular experience in working with doulas. The hospitals from Group A showed indifference towards working with doulas. Group B declared a positive attitude towards such cooperation. Attitudes towards doulas vary among executives and are related to the frequency of doula‐assisted births. Our results indicate factors that may influence the attitude of medical staff towards doulas and which may contribute to improve future initiatives meant to facilitate collaboration between midwives and doulas. Patient or Public Contribution This study explored the lived experiences of perinatal care managers.